Pezizales (Ascomycota) associated with pine-oak forest in Yécora, Sonora, Mexico - Madriz-Valdovinos, David; Raymundo, Tania; Gutiérrez, Aldo; Sánchez Flores, Marcos; L. Coronado, Martha; Esqueda, Martín (Instituto de Ecología, A.C., 2022)
Background and Aims: Pezizales is one of the most studied orders of the kingdom Fungi in the world and the second-best known group of ascomycetes in Mexico with 185 species; on the contrary, there are only 23 species registered for Sonora. The aim of this study was determined the taxonomic richness of Pezizales associated with the pine-oak forest in one locality of municipality of Yécora, Sonora, Mexico.Methods: Five seasonal samplings were carried out in pine-oak forest of Los Pilares, Yécora, Sonora during the years 2020-2021. The taxonomic determination was made with specialized keys from the macro- and micromorphological characterization of the specimens.Key results: Sixteen Pezizales species distributed in seven families were determined: Helvellaceae (5), Pezizaceae (2), Pseudombrophilaceae (1), Pulvinulaceae (1), Pyronemataceae (4), Sarcosomataceae (1), and Sarcoscyphaceae (2). Twelve species are new records for Sonora and six for Mexico: Geopyxis deceptiva, Helvella dryophila, Plectania milleri, Pseudombrophila fuscolilacina, Pseudopithyella magnispora and Tricophaeopsis latispora. In addition, the last three taxa are cited for the first time for the American continent.Conclusions: The Sonoran Pezizales catalogue increased to 35 taxa; however, it is important to continue with studies, which include ecological and phylogenetic analyzes of this group of fungi.